MMP-7, -8, -9, E-cadherin, and beta-catenin expression in 34 ameloblastoma cases - Kelppe Jetta; Thoren Hanna; Haglund Caj; Sorsa Timo; Hagström Jaana (WILEY, 2022)
Objectives
Ameloblastoma is a benign, locally aggressive odontogenic tumor with high recurrence rates. Matrix metalloproteinases (MMPs) mediate extracellular integrity in normal and pathological conditions, and exert multiple functions coordinating inflammation and tumor progression. E-cadherin and beta-catenin are adherence junction molecules in cell-to-cell connections. We investigated the involvement of MMP-7, -8, -9, E-cadherin, and beta-catenin in ameloblastoma and the surrounding extracellular matrix.
Material and methods
Our material consisted of 30-34 tissue samples from ameloblastoma patients of Helsinki University Hospital. We used immunohistochemistry to detect the expression of the biomarkers. Two oral pathologists independently scored the immunoexpression intensities and statistical calculations were made based on the results.
Results
E-cadherin expression was weaker in the maxillary than in mandibular ameloblastomas. Beta-catenin was expressed in the ameloblastoma cell membranes. We detected MMP-8 and -9 expression in polymorphonuclear neutrophils in the extracellular area and these MMPs correlated positively with each other. Osteoclasts lining bone margins and multinuclear giant cells expressed MMP-9. Neither MMP-8 nor MMP-9 immunoexpression could be detected in ameloblastoma cells. MMP-7 expression was seen in some apoptotic cells.
Conclusion
The fact that E-cadherin immunoexpression was weaker in maxillary compared to mandibular ameloblastomas might associate to earlier recurrences. It promotes the idea of mandibular and maxillary ameloblastoma exerting differences in their biologies. We detected MMP-8 and -9 in polymorphonuclear neutrophils which relates to these MMPs participating in extracellular remodeling through a mild inflammatory process. Bone degradation around ameloblastoma may be due to MMP-9 in osteoclasts but this phenomenon might be an independent process and needs further investigations.